Necesidad de regular el procedimiento en la Ley de la Jurisdicción Contenciosa administrativa para la aplicación del silencio administrativo - Zhunio Ordoñez, Fredy Moisés (2015)
Article 66 paragraph 23 of the Constitution recognizes "the right to lodge complaints and petitions to the authorities, but in no case on behalf of the people, and to receive attention or relevant answers in a timely fashion." However, within the State Modernization Act does not establish the legal parameters and effect of protecting the public when dealing with the inactivity of the administration. Given the problems described above I decided to make this research work titled "LEGAL ANALYSIS doctrinal and administrative silence" in which I make a doctrinal and legal analysis of the issues raised, we show here the failure of the law and the urgent need to create a legal rules that allow a better implementation of administrative silence. Therefore in this paper reflected the theoretical arguments, results of field research, in which analysis shows the need to create a legal system that allows better application of administrative silence, being the main point of my thesis work , which I hope will help solve this problem